SIMBES, Aplikasi Manajemen Beasiswa di Universitas Diponegoro Berbasis Framework Code Igniter dan MySQL - Muchamad Shodiq; Kodrat Iman Satoto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2013)
Scholarship is a very important need for the students to be able to continue their education, especially for disadvantaged groups as well as achievement. Diponegoro University as one of the State institutions strive to provide assistance in the form of scholarships for students to be able to carry out their studies. However, the distribution of these scholarships often have many constraints experienced by students as time is too sudden, and difficulties in completing other requirements. Application Scholarship Information Systems, University of Diponegoro is one way to overcome the distribution of scholarships at the University of Diponegoro. This application helps in increasing the speed of Diponegoro University and management in the distribution of scholarships to students.The stage in this application uses several stages of literature and guidance, data collection and analysis (interviews, observations and information files), design, manufacture of system / application and final implementation commonly referred to as the waterfall method. This method is very appropriate in this study because it has applications like workflow that allows designers to evaluate the application without having to change from the bottom. While the design of the application using UML modeling.This application is based on the Code Igniter framework which uses MVC method (Model, View, Controller) with every event organized by function application specified in the controller. In the testing phase, the application was tested in the scope of its functions. As a result, every function can be run smoothly and Information Systems Scholarship applications can be implemented. Information Systems Scholarship applications can run smoothly in the Code Igniter framework along with its functions. However, these applications are not fully using the PHP programming language in its function, there are languages that work client side Javascript that helps in performing certain functions. It is recommended not to disable javascript in a user's browser or will affect the application does not work properly.